Impact of Earthquake on Migration A Post-Earthquake Assessment: The Case of Sankhu, Kathmandu - Shrestha, Madan Gopal (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2021)
The central objective of this study was to explore to assess the immediate impact of the 2015 Earthquake on Livelihood. Limited studies were carried out after the 2015 earthquake, except for a few notes no academic research was available till the period of this research done about Sankhu. Here the researcher himself from Sankhu tried to explore the Post-earthquake Impacts of Migration a historic town in Sankhu. This study was based on the qualitative research methodology, and revealed, immigration started in the community that has a lot of impact on culture, economy, and infrastructure in the community. Historically, since the Panchayat regime, there was no trend of immigration. The purpose of out-migration was for education to business. On one hand, the 2015 earthquake forced them to migrate from Sankhu and on another hand, the implication 2015 earthquake on migration forced people to change their residences and different parameters of livelihoods. The results of this study conclude that volume of migration within the Sankhu is higher than the volume of migration outsides to the Sankhu, short distance migration preferred after the 2015 earthquake. The immediate impact of the 2015 earthquake was on infrastructure, occupation, education, health, the culture which are the means of livelihood, several displacements was the first step of the impact of the 2015 earthquake before migration for better livelihoods. We observed that migration is selective, our study reveals that priority basis migration with the selection of opportunity of earning, place either at the vicinity of Sankhu or Kathmandu city. As well as the recent change of center place in Sankhu proved by members of business enterprises increasing surrounding the Sankhu than Sankhu town inside which was a historic business place. The people who are staying in Sankhu struggling with difficulties for better Livelihoods destroyed.